PENDIDIKAN DIET SEHAT DI ERA PANDEMI COVID-19 DENGAN MEDIA KOMIK DAN KARTU GIZI PADA ANAK DI WILAYAH KECAMATAN PANCENG, GRESIK - Ika Nur Pratiwi; Lingga Curnia Dewi; Lailatun Nimah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The government issued an online learning model policy as an effort to minimize the transmission of COVID-19 in children. However, the transmission of COVID-19 is still affecting children. To prevent the spread of the virus with the immune system through a balanced nutritional lifestyle. The purpose of this community service (PKM) is to provide education on a healthy diet for children in the era of the COVID-19 pandemic using comics and nutrition cards. Location of PKM activities at UPT SD Negeri 314 Gresik with due observance of strict health protocols. The PKM method uses a Community Based Research (CBR) approach through education and nutrition card games. Final evaluation of the PKM program by comparing the pre-test and post-test scores on knowledge about balanced nutrition. The results of PKM, there are 69 students (33 male students and 36 female students) where there is a difference in knowledge p = 0.000 (p <0.05) before and after education. Empowerment of elementary school students through education about a healthy diet and balanced nutrition can be an effort to increase body resistance in the pandemic era.